2009
DOI: 10.1111/j.1439-0434.2008.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Begomoviruses Associated with Yellow Leaf Curl Disease of Tomato in Iran*

Abstract: The occurrence of Tomato yellow leaf curl virus (TYL-CV; genus Begomovirus, family Geminiviridae) in the major tomato-growing areas of Iran was determined using TAS-ELISA and PCR. The nucleotide sequences of the coat protein (CP) gene and intergenic region (IR) of eight Iranian isolates were determined. CP nucleotide identities among the Iranian isolates were 96-98%, and showed 94-96% identity with TYLCV-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…On the basis of partial sequences of CP and MP, studied isolates were categorized into two major groups. Iranian isolates had previously been divided into two groups on the basis of IR (Intergenic Region) sequences (Bananej et al, 2008). These data emphasized that studied isolates were distinct from each other's based on geographical distribution and not by host range.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…On the basis of partial sequences of CP and MP, studied isolates were categorized into two major groups. Iranian isolates had previously been divided into two groups on the basis of IR (Intergenic Region) sequences (Bananej et al, 2008). These data emphasized that studied isolates were distinct from each other's based on geographical distribution and not by host range.…”
Section: Discussionmentioning
confidence: 83%
“…In the last few decades, TYLCV is expanding rapidly and new infected areas have been reported in several parts of the world especially in the New World. In Iran, since the first report of TYLCV from Southern provinces including Sistan and Baluchestan, Hormozgan, Kerman, Boushehr and Khuzestan (Hajimorad et al, 1996), it was reported in Khorasan, Isfahan, Markazi, Golestan, Tehran and Yazd (Shahriary and Bananej, 1998;Bananej et al, 1998Bananej et al, , 2004Bananej et al, , 2008. Although TYLCV was known as an infecting pathogen of tomato (Solanum lycopersicum), it can also infect several crop plants such as bean (Phaseolus vulgaris L.), lisianthus (Eustomus grandiflorum), Mercurialis ambigua and pepper (Capsicum annum) (Cohen and Gera, 1995;Navas-Castillo et al, 1999;Reina et al, 1999;Sanchez-Campos et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, TYLCD-associated virus isolates belonging to two or more different species, and sometimes recombinants, have been found in the same country [3][4][5][6][7][8]. This disease was first identified in Israel in 1930 and has since the 1960s become the most important tomato viral disease in different countries [9][10][11][12][13][14]. In Iran, TYLCV was first reported in 1996 from central and southern provinces of Iran (Kerman, Hormozgn, Khuzestan, Bushehr, and Sistan-Baluchestan) [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…This disease was first identified in Israel in 1930 and has since the 1960s become the most important tomato viral disease in different countries [9][10][11][12][13][14]. In Iran, TYLCV was first reported in 1996 from central and southern provinces of Iran (Kerman, Hormozgn, Khuzestan, Bushehr, and Sistan-Baluchestan) [9,13]. The Lycopersicon esculentum is the primary host of TYLCV [15].…”
Section: Introductionmentioning
confidence: 99%